Reasons for SARS-CoV-2 infection in children and their role in the transmission of infection according to age: a case-control study - Mauro Calvani; Giulia Cantiello; Maria Cavani; Eleonora Lacorte; Bruno Mariani; Valentina Panetta; Pasquale Parisi; Gabriella Parisi; Federica Roccabella; Paola Silvestri; Nicola Vanacore (BMC, 2021)
Abstract Background The locations where children get exposed to SARS-CoV-2 infection and their contribution in spreading the infection are still not fully understood. Aim of the article is to verify the most frequent reasons for SARS-CoV-2 infection in children and their role in the secondary transmission of the infection. Methods A case-control study was performed in all SARS-CoV-2 positive children (n = 81) and an equal number of age- and sex- matched controls who were referred to the S. Camillo-Forlanini Pediatric Walk-in Center of Rome. The results of all SARS-CoV-2 nasopharyngeal swabs performed in children aged < 18 years from October 16 to December 19, 2020 were analyzed. Results School contacts were more frequent in controls than in cases (OR 0.49; 95% CI: 0.3-0.9), while household contacts were higher in cases (OR 5.09; 95% CI: 2.2-12.0). In both cases and controls, school contacts were significantly less frequent, while on the contrary household contacts seemed to be more frequent in nursery school children compared to primary school or middle/high school children. A multivariate logistic regression showed that the probability of being positive to SARS-CoV-2 was significantly lower in children who had school contacts or who had flu symptoms compared to children who had household contacts. Results showed a 30.6% secondary attack rate for household contacts. Conclusion In our study population, the two most frequent reasons for SARS-CoV-2 infection were school and home contacts. The risk of being positive was 5 times lower in children who had school contacts than in children who had household contacts.